2019
DOI: 10.1053/j.gastro.2018.11.081
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, Cell Biology, and Pathophysiology of Pancreatitis

Abstract: Since the discovery of the first trypsinogen mutation in families with hereditary pancreatitis, pancreatic genetics has made rapid progress. The identification of mutations in genes involved in the digestive protease-antiprotease pathway has lent additional support to the notion that pancreatitis is a disease of autodigestion. Clinical and experimental observations have provided compelling evidence that premature intrapancreatic activation of digestive proteases is critical in pancreatitis onset. However, dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
200
0
25

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(227 citation statements)
references
References 198 publications
(256 reference statements)
2
200
0
25
Order By: Relevance
“…Excessive oxidative stress is one of the most important causes of cell injury in acute inflammatory diseases [11]. Studies have indicated that oxidative stress and the related production of reactive oxygen species (ROS) play a major role in pancreatic acinar cell injury in AP [12,13]. Moreover, many studies suggest that antioxidant treatment can effectively reduce pancreatic tissue damage and inflammatory response in mice of AP, such as carbon monoxide-bound hemoglobin vesicle [14], coenzyme Q10 [15], and isoliquiritigenin we reported earlier [16].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive oxidative stress is one of the most important causes of cell injury in acute inflammatory diseases [11]. Studies have indicated that oxidative stress and the related production of reactive oxygen species (ROS) play a major role in pancreatic acinar cell injury in AP [12,13]. Moreover, many studies suggest that antioxidant treatment can effectively reduce pancreatic tissue damage and inflammatory response in mice of AP, such as carbon monoxide-bound hemoglobin vesicle [14], coenzyme Q10 [15], and isoliquiritigenin we reported earlier [16].…”
Section: Introductionmentioning
confidence: 99%
“…Monocytes and macrophages are part of the innate immune system and exhibit a high degree of plasticity. Activated pro-inflammatory macrophages (M1) release copious amounts of cytokines, including interleukin 6 (IL6), IL12, IL1β and tumour necrosis factor alpha (TNFα), early in the inflammatory response and in AP make a significant contribution to the systemic inflammatory response syndrome linked to organ dysfunction and death [12]. Recently extra-acinar protease activation within macrophages during endocytosis of zymogen-containing vesicles has been shown to participate in the systemic inflammatory response and determine AP severity [39].…”
Section: Discussionmentioning
confidence: 99%
“…This may partly reflect the significant challenge posed by the isolation of patient blood cells in a reliable state for such bioenergetics measurements. In recent years, there has been increasing focus on the roles of immune cell subsets in the systemic inflammatory response in AP [11,12]. For example, neutrophil infiltration is evident in the pancreas within minutes of the onset of AP and exerts a significant role in disease severity [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Merke Eine akute Entzündungsreaktion geht einer chronischen Pankreatitis wohl in der Regel voraus, ist aber keine absolute Voraussetzung dafür [11,13].…”
Section: Störungen Durch Alkohol Folgen Funktionelle Störungenunclassified
“…a. durch eine reduzierte Kapazität der Trypsininhibition und erhöhten intrazellulären oxidativen Stress. Auch eine gleichzeitig bestehende Hyperlipidämie erhöht das Risiko einer akuten Pankreatitis [11,13].…”
Section: Individuelle Prädispositionunclassified